1cm origin - Kim, Eun-Ju (Quezon City, Philippines : Adarna House Inc., 2021)
1cm is the book that asks you to take a break from the difficulties of the world to enjoy something 1cm different! This is the first-ever English transition to the Korean bestseller that has sold more than 1 million copies worldwide! Filled with beautiful illustrations and fun interactive activities, 1cm will share unique insights about the things you already know but take for granted. (3z(BIf our life is like bread slices, happiness is like the jam between them. It$1 (Bs hidden but it makes life sweet.(3y (BTO THINK - See a new world by moving 1cm away from your stereotypes. TO LOVE - Move 1cm closer and surprise yourself with new experiences of love. TO OPEN - See 1cm deeper and get to know people in your life better. TO RELAX - Breath 1cm longer and appreciate your daily life more. TO GROW - Grow 1cm every day, and see how much you improve over time.s
Keywords: HAPPINESS